Effects of tDCS stimulation on exercise performance and changes in MRCP amplitude - Sung, Dong-Jin; Jeong, Ji Hyeok; Yeo, Sang-Hoon; Kim, Hyungmin (Brain Stimulation, 2023)
Various studies investigated the use of non-invasive neuromodulation techniques such as transcranial direct current stimulation (tDCS) to assess their ergogenic effects. However, it is still unknown whether such ergogenic effects accompany changes in brain oscillation patterns detectable by EEG. In the present study, we focused on the excitatory effect of anodal tDCS, and tested whether receiving tDCS prior to exercise 1) increases the performance of the exercise and 2) results in differentiable EEG components. Seven healthy male participants (age = 28.1 ± 3.0 yrs, weight = 79.5 ± 10.1 kg, height = 178.8 ± 7.3 cm) volunteered to participate in the randomized, crossover, single-blinded experiment consisting of two sessions. A session included two trials of EEG data acquisition while consecutively stepping on a foot pedal to acquire movement-related cortical potential (MRCP). Each trial was performed before and after 20 minutes of either sham or real tDCS (anodal, 1 mA) over M1. The changes in MRCP amplitude after each stimulation were examined. Subsequently, the participants performed a maximal incremental exercise test until volitional exhaustion on a treadmill. Breath-by-breath pulmonary gas exchange measurements were collected during the protocol. Exercise performance was evaluated by analyzing maximal oxygen intake (VO2 max) and energy expenditure (EE). Compared to sham, tDCS led to an increase in VO2 max (t(6) = -3.1, p = 0.02). Similarly, higher EE was seen in stimulated subjects (t(6) = -3.4, p = 0.01). In addition, the changes in MRCP amplitude after tDCS were significantly different compared to sham conditions (t(6) = -2.7, p = 0.03). These results indicate that anodal tDCS prior to exercise enhances exercise performance and also induces differentiable MRCP amplitudes that are observable after stimulation.